Trade policy, trade volumes and plant-level productivity in Colombian manufacturing industries - Ana Fernandes (Yale University, Economic Growth Center, 2002)
This paper offers new insights on a central question in trade and development economics: does increased exposure to foreign competition generate gains in plant productivity? We find that it does. We examine Colombian trade policy from 1977 to 1991, a period during which trade liberalization alternates with increased trade protection in varied ways across industries, to investigate the link between trade policy and plant productivity. Using a rich panel of manufacturing plants, we obtain production function estimates separately across industries that are consistent in face of the simultaneity between input demands and productivity. These estimates are used to derive plant-level time-varying productivity measures for which a systematic component related to trade policy is identified. We find a strong negative impact of nominal tariffs on plant productivity controlling for observed and unobserved plant characteristics and industry heterogeneity. The use of lagged tariffs and the evidence on the political economy of tariff determination in Colombia allow us to argue that the negative impact of tariffs is unlikely to reflect the endogeneity of protection. Plant exit plays a minor role in generating productivity gains in face of lower trade protection. Also, accounting for variation in the Colombian peso's real exchange rate does not weaken the main findings. The negative impact of trade protection on productivity is stronger for large plants relative to small plants, as measured by employment and market shares. The negative impact of trade protection on productivity is stronger for plants in less competitive industries according to Herfindahl indexes and turnover rates. The main findings are robust to the use of effective rates of protection and import penetration ratios as measures of trade protection and openness. Finally, we also find evidence of a negative impact of trade protection on the rate of growth of plant productivity.
Keywords: F13; D24; C14; O54; 330; Simultaneity and Production Functions; Trade Policy; Productivity; Colombian Manufacturing; Endogeneity of Protection